2006
DOI: 10.1620/tjem.210.79
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Presentation of Tuberculosis as a Splenic Mass

Abstract: Tuberculosis is an important health problem in developing countries, with varying clinical presentations depending on the organs/systems involved. Tuberculosis is mostly seen in immuno-compromised individuals, such as those with acquired immune deficiency syndrome or malignancies. Here we report a case of a spleen tuberculoma in a 29-year-old male patient with no known immune deficiency. He first presented with abdominal pain, and subsequent ultrosonographic examination revealed a splenic lesion of 10 cm in di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…The more frequent form is the disseminated or miliary type involving the spleen which often is related to immunosuppressed condition but also is observed in immunocompetent patients (5, 11). The isolated type is rare and has been reported to be more associated with HIV infection (5, 12). Our patient did not have a specific HIV antibody test, but with regard to the normal laboratory results listed previously, the possibility of concurrent HIV infection is less likely.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The more frequent form is the disseminated or miliary type involving the spleen which often is related to immunosuppressed condition but also is observed in immunocompetent patients (5, 11). The isolated type is rare and has been reported to be more associated with HIV infection (5, 12). Our patient did not have a specific HIV antibody test, but with regard to the normal laboratory results listed previously, the possibility of concurrent HIV infection is less likely.…”
Section: Discussionmentioning
confidence: 99%
“…If the nodules are below the resolution capability of imaging techniques, they could manifest as simple splenomegaly (10). Macronodular splenic tuberculosis is rare and could manifest as a singular abscess or multiple large nodules (12). If it does manifest as a localized mass as in our case, differentiation from other solid mass lesions is not always easy (12, 15).…”
Section: Discussionmentioning
confidence: 99%
“…9 As most patients with splenic tuberculosis may have disseminated disease, a few controlled trials of treatment in patients with extra-pulmonary tuberculosis strongly suggest a 12-month regimen, with prolonged treatment if deemed necessary. 13,14 In contrast, one study showed very slight improvement between imaging studies at 12 and 24 months although anti-tuberculous treatment was continued for over 24 months due to unresolved lesions. 13 The optimal duration of treatment for splenic tuberculosis is undetermined: in our case, further treatment was discontinued after nine months of anti-tuberculous medication since most of the lesions had disappeared.…”
Section: Discussionmentioning
confidence: 99%
“…However several authors describe in their work splenic tuberculosis. Dede et al (15) described the case of a 29-year-old patient with widespread abdominal pain worsening for 6 mo. In performed exams showed enlarged, thick walled centrally necrotic mass lesion at the upper pole of the spleen.…”
Section: Discussionmentioning
confidence: 99%